Corporate Sustainability And Working Capital Management Efficiency In Emerging Markets: Evidence From Listed Firms In Nigeria - Mbah, Fatima Imika; Olowookere, Johnson Kolawole; Olagunju, Adebayo; Oladejo, Titilayo Moroomoke (Universitas Indonesia Membangun, 2025)
Corporate sustainability, previously viewed through environmental, social, and governance (ESG) lenses, is now integral to strategic and financial performance. This study investigates the impact of corporate sustainability on the working capital management efficiency (WCME) of listed companies in Nigeria. Drawing on stakeholder theory and resource-based theory, the study conceptualizes corporate sustainability in a composite perspective and assesses its impact on WCME. The empirical analysis utilizes panel data from listed non-financial firms (2014 – 2024). The findings revealed that corporate sustainability performance exerts an adverse and statistically noteworthy effect on both the cash conversion cycle (CCC) and the WCME score. The findings have recommendations for policymakers, corporate managers, and investors, highlighting the need for firms to develop strategies that facilitate efficient working capital management while pursuing sustainability. The policymakers and firm managers must maintain this balance, to ensure sustained operational performance and the overall financial health of the firms.